Amorphous 2D‐Nanoplatelets of Red Phosphorus Obtained by Liquid‐Phase Exfoliation Yield High Areal Capacity Na‐Ion Battery Anodes. Issue 6 (23rd December 2022) - Kaur, Harneet; Konkena, Bharathi; Gabbett, Cian; Smith, Ross; McCrystall, Mark; Tian, Ruiyuan; Roy, Ahin; Carey, Tian; Vega‐Mayoral, Victor; Nicolosi, Valeria; Coleman, Jonathan N.
Abstract: The development of sodium ion batteries will require high‐performance electrodes with very large areal capacity and reasonable rate performance. Although red phosphorus is a very promising electrode material, it has not yet fulfilled these requirements. Here, liquid phase exfoliation is used to convert solid red phosphorus into amorphous, quasi‐2D nanoplatelets. These nanoplatelets have lateral sizes of hundreds of nanometers, thickness of 10s of nanometers and are quite stable in ambient conditions, displaying only low levels of oxidation on the nanosheet surface. By solution mixing with carbon nanotubes, these nanoplatelets can be fabricated into nanocomposite battery anodes. After employing an extended activation process, good cycling stability over 1000 cycles and low‐rate capacitances >2000 mAh gP −1 is achieved. Because of the high conductivity and mechanical robustness provided by the nanotube network, it is possible to fabricate very thick electrodes. These electrodes display extremely high areal capacities approaching 10 mAh cm −2 at currents of ≈1 mA cm −2 . Detailed analysis shows these electrodes to be limited by solid‐state diffusion such that the thickest electrodes have state‐of‐the‐art rate performance and a near‐optimized combination of capacity and rate performance. Abstract : Liquid phase exfoliation is used to synthesize 2D‐nanoplatelets of red‐phosphorus. These nanoplatelets are used to make electrodes for sodium‐ion batteries using carbon nanotubes as both binder and conductive additive. The electrodes display good stability over 1000 cycles and excellent low‐rate capacities >2000 mAh g −1 . The thick electrodes display very high areal capacities of 10 mAh cm −2 at 1 mA cm −2 .